Sosialisasi Manfaat Eco Enzyme Sebagai Solusi Ramah Lingkungan Dalam Pengelolahan Limbah Organik di SD Negeri 105327 Pardamean - Putri Juwita; Lasni Roha Tampubolon; Kenzi Utama Putra; Khairuna Haflah Maula Harahap; Lailan Safitri Barus; Lely Sriwahyuni; Laurentia N Hutauruk; Marisa Marisa; Lidia Merda (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract The accumulation of organic waste and the excessive use of chemical fertilizers represent significant environmental problems in Indonesia. Eco Enzyme emerges as an innovative solution, offering a sustainable alternative for organic waste management and fertilization. A socialization and training program on Eco Enzyme production was conducted at SD Negeri 105327 Pardamean, Tanjung Morawa District, involving 15 practitioners. The methods employed included material presentations and practical training in Eco Enzyme production from vegetable and fruit waste. The program's evaluation was conducted by comparing pre-test and post-test results. The evaluation results showed an 81.3% increase in participants' understanding and skills after attending the socialization and training. This indicates the effectiveness of the activity in enhancing participants' knowledge and ability to independently produce Eco Enzyme in household settings. It is expected that this activity can positively contribute to improved organic waste management and reduce reliance on synthetic chemical fertilizers.